Proposta de zoneamento ecológico-econômico como instrumento de desenvolvimento sustentável: subsídios para o planejamento ambiental na construção do Distrito de Covalima – Timor-Leste - Cruz, Rui António da (2012)
The Covalima located in southwestern Democratic Republic of Timor-Leste-RDTL constituted country under a democratic rule of law, sovereign and independent, unitary, based on the popular will and respect for human dignity and the right to an environment a humane, healthy and ecologically balanced and duty to protect and enhance and support of future generations. Recognizing the need to preserve and enhance natural resources, and promote actions to protect the environment and safeguard the sustainable development of economy, stressing that the use of natural resources to maintain balance and prevent destruction of ecosystems. Is attributed to the significant meaning in this present study, to establish Proposal for ecological-Economic-ZEE as a tool for sustainable development. Subsidizes environmental planning is seeking to reconcile the human behavior on the basis of appropriate environmental management, to improve the use of natural resources in the process of sustainable environmental. There was bias from the socio-environmental theoretical framework which shows the relationship between society and nature, claiming self-conscientization, respecting the carrying capacity of nature. It is based on the basis of zoning in which the organization affects the democratic power of public policy, assuming the role of environmental planning and management. Is directed, so the strategic plans focusing on the use and occupancy of the land in search for the rehabilitation and maintenance of functional integrity of environmental systems. Avoidance of negative impacts and consequences of natural biophysical systems, besides the quality of life of the population on the basis of sustainable development. The establishment of the geoenvironmental characteristics, socioeconomic and use of land occupation, based on the reasoning of the zoning application of analytical techniques for digital satellite (TM / LANDSAT 7 ETM + 2000) and GIS, with prior knowledge, as well as documents bibliographic and geocartographic. Resulted in the subdivision within 5(five) environmental Systems, 8 (eight) sub-systems and socioeconomic aspects, allowing to determine the classification of 6 (six) areas of interest, uniquely adopting the definition and function the same as: Zone Environmental Conservation, Zone of the Environmental Recovery-ZRA, Sustainable Use Zone-ZUS, Landscape Protection Zone and Cultural-ZPPc, Urban Zone Expansion-ZEU, Ethnic-Zone Overlay-ZSE. It is obvious that the uniqueness of the function of each zone meets in contributing to dispose finally of the Zoning Environmental generating the emerging scenarios that the system provides for Sustainable Development in the construction of Covalima. It is intended that this zoning will help to subsidize the public politics of Timor-Leste in the pursuit of sustainable development Covalima.